Penguatan Modal Sosial Dalam Implementasi Pelayanan Kesehatan Berkeadilan Gender: Contraceptive for Woman at Risk (Contra WaR) - Alifiulahtin Utaminingsih (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This article presents the results of research on social capital and innovation of public service in the field of maternal and child health called (Contra WaR). Social capital and public service innovation are assumed to be able to lower the risk of women while program pregnancy until childbirth. This research was conducted in Malang district, using a case study approach with data collection techniques in deep observation and interviews. The informant is determined using the purposive sampling i.e. the relevant Dinas, women married to the fertile age, who are pregnant and at high risk. The results showed that the social capital in the form of value and norms, network and trust are able to erode the views of Javanese people who declare many children a lot of sustenance to multiply offspring. Implementation of the Strategy innovation Contra WaR; First, integrated services; Secondly, creating a social network that focuses on pregnancy delays for women of childbearing age who have a high risk of illness; Third, community involvement as a health cadre; Fourth, the utilization of information and communication technology accelerates the socialization of proper contraceptive use according to the disease he sustained. The supporting factors of the program Contra WaR is increasing public awareness to healthy living, the establishment of field officers and cadres. While the inhibitory factor is the lack of level of compliance of field officers, the trust of many children is a lot of sustenance.